(untitled) (Zoological Records and Reviews, 2021)
Andhra Pradesh, situated at the interface of the Eastern Ghats and the Deccan Plateau, harbours a poorly inventoried amphibian fauna despite its high topographic and ecological heterogeneity. This study presents integrated morphological and molecular characterization of 14 amphibian species sampled from six districts of Andhra Pradesh during the monsoon seasons of 2018 and 2019. Morphometric measurements (18 variables per individual) and qualitative characters (skin texture, toe-webbing, tympanum visibility, and colouration) were recorded for 284 individuals across Anura (12 species) and Gymnophiona (2 species). Mitochondrial 16S rRNA gene sequences (550 bp) were generated for 84 individuals. Bayesian phylogenetic analysis resolved seven well-supported clades congruent with current family-level taxonomy. Morphometric discriminant function analysis correctly assigned 91.4% of individuals to their species based on eight morphometric ratios. Two populations of Nyctibatrachus cf. humayuni from the Nallamala Hills exhibited 16S pairwise distances of 6.8-7.4% from reference sequences, suggesting the presence of at least one undescribed species. Species distribution models fitted to climatic predictors identified 34.2% of suitable habitat as falling outside existing protected area boundaries, highlighting substantial gaps in the current protected-area network for amphibian conservation in Andhra Pradesh.